WHITHER “HEARTLAND”? CENTRAL ASIA, GEOGRAPHY AND GLOBALIZATION - HEKIMOGLU, Levent (CENTRAL ASIA AND THE CAUCASUS, 2005)
This article attempts a double task. First, it looks at the main premises of Halford J. Mackinder’s analysis in his renowned 1904 address to the Royal Geographical Society, The Geographical Pivot of History, and discusses some of the problems. It observes that these problems have actually rendered the whole Heartland thesis a fallacy from its very inception and argues that this resilient fallacy continues to distort perceptions and policies in/on Central Asia. Second, it draws attention to the severe geographical predicament of Central Asia in an era of rapid globalization and points out how a host of myths led by the ghost of Mackinder’s Heartland, in conjunction with the biases and flaws of neoliberal dogma, serve to impede the development of strategies for dealing with that predicament.The landlocked interior of the Eurasian continent was called the “Heartland” and “the Pivot area” in Mackinder’s 1904 address, not because he attributed some metaphysical intrinsic strategic quality to the region, but because he believed that the region possessed vast natural resources, including a huge agricultural potential. He was convinced that thanks to the revolution in land transportation recently brought about by railroad technology, Inner/Central Asia was destined to provide its contemporary political master with an unequalled economic capability, becoming the engine of an inevitable Russian bid for world dominance.Mackinder’s confidence in the commercial competitiveness of railroads with maritime transport and in the vastness of resources in Inner/Central Asia both have turned out to be misplaced. The region couldn’t have and has not lived up to the “pivot” billing given to it by Mackinder. The Heartland thesis has survived not on account of the validity of the underlying premises and the merits of the argument, but because its conclusions recommending the containment of Russia fit snuggly into the Cold War ideational scheme that dominated much of the 20th century.The ghost of the Heartland fallacy is still very much around, and it is not a benign one.